2010
DOI: 10.1159/000319323
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Hartmann’s Procedure after Perforated Diverticulitis through the Stomal Side without Additional Incisions: The SIR Procedure

Abstract: Aims: Reversal of Hartmann’s procedure (HP) is a complex operation and only performed in 50–60% of the patients. Stomal incision reversal (SIR), a new minimally invasive procedure for HP reversal, was assessed and compared to the standard surgical approach. Methods: 16 patients who had undergone HP for perforated diverticulitis underwent HP reversal by SIR. The only incision in SIR is the one to release the end colostomy. Intra-abdominal adhesiolysis is done manually. A stapled end-to-end colorectal anastomosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…The minimal invasive technique of Hartmann reversal using the stoma site as a single incision site has been introduced and described with favorable results compared with laparotomy, such as the stoma incision reversal (SIR) procedure reported by Vermeulen et al [23,24]. However, the SIR procedure does not employ laparoscopic access to the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal invasive technique of Hartmann reversal using the stoma site as a single incision site has been introduced and described with favorable results compared with laparotomy, such as the stoma incision reversal (SIR) procedure reported by Vermeulen et al [23,24]. However, the SIR procedure does not employ laparoscopic access to the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…One author describes the reversal through the stomal side with manually adhesiolysis and manually controlled anastomosis [2]. In open surgery, Kunin et al [3] described a morbidity of 47,8% and a mortality of 4,3% after reversal of Hartmann's operation.…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of extra incisions, pain and possible complications by multiport access is one big advantage of single-port surgery combined with a better cosmetic result (Table 4). Access through the stomal side and manually preparation without laparoscopic instruments showed a conversion rate of 19% [2] and is therefore not recommended by us.…”
Section: Discussionmentioning
confidence: 99%
“…Other minimally invasive techniques for RHP have been described, such as the so-called stoma incision reversal (SIR) procedure reported by Vermeulen et al 19 Here the stoma is mobilized as in our technique, and any further adhesiolysis and stapled anastomosis are performed through the same stoma incision. The authors have reported results from a case series of 16 patients, 3 of which were converted to a standard laparotomy approach.…”
Section: Discussionmentioning
confidence: 99%